Competences for the application of the nursing process: self-evaluation of the students that are completing the requirements for the undergraduation course - Fontes, Wilma Dias de; Leadebal, Oriana Deyze Correia Paiva; Ferreira, Jocelly de Araújo (Rev Rene, 2010)
The teaching of nursing process has represented a challenge in the professional formation, which calls for the enhancement of coping with the professionals of the area. This is an exploratory-descriptive study, which investigated the skills, knowledge and abilities of gra- duating students to implement the nursing process, developed in Joao Pessoa PB, from June to December 2007 in three Higher Education institutions; the samples were 97 students, and as instrument it was used the Likert questionnaire, based on skills prepared by National Curriculum Guidelines for Undergraduate Courses in Nursing and the pertinent literature. The results were analyzed quantitatively, re- vealing that the majority agrees with the possession of skills, knowledge and ability to implement the steps of the nursing process, even when one of those skills stood out against the other, a fact that raises thoughts about the contribution of theory and practice integration in academic education.